Verbal analysis of the investment risk in construction - Ustinovičius, Leonas; Kochin, Dmitry (Journal of Business Economics and Management, 2003)
Obtaining of reliable enough estimations of investment quality is a complex task, since there is no universal indicator of capital recovery probability. Classification is a very important aspect in decision making. This means the prescription of projects to the particular classes. Very often it is stated that classes in decision making are determined by the particular parameters, i.e. the efficiency of technical and technological decisions, credit value determination of the project, etc. This article presents a verbal method of determining investment risk in construction. The problem under consideration is investment assessment depending on the risk level. Formally the problem is stated as multicriteria classification one. A hierarchical approach to considered effectiveness indicators is proposed. The proof of effectiveness of the method is presented. A procedure of method application is described for a practical task.First Published Online: 14 Oct 2010